Trends in clinical presentation and treatment outcomes in a South African TTP cohort - Vundla, Nokubonga (Department of Medicine, 2024)
Background: HIV is the most common cause of secondary thrombotic thrombocytopenic purpura (TTP) in South Africa. Objectives: To assess the clinical presentations and outcomes of patients treated for HIV-associated and idiopathic TTP. Methods: We conducted a retrospective cohort study of patients consecutively diagnosed with TTP from 2010 to 2020 at Groote Schuur Hospital. Study participants were identified by reviewing patient files and Western Cape Blood Services records. Kaplan-Meier curves and log-rank tests were used to evaluate remission rates overall and, by HIV status and treatment group. Logistic regression models were used to identify predictors of remission and relapse. Results: 139 patients were included, 85.6% of whom were HIV positive. There were no significant differences in the TTP pentad features by HIV status. Most patients achieved remission (71.9%) with an overall median time of 8 days. Remission occurred significantly earlier in those treated with FFPs only, suggesting less severe disease (median=8 days [IQR 6-10]), compared to those requiring the addition of plasma exchange suggesting more severe disease (median=12 days [IQR 8-22]). The overall mortality in the 10-year period was 38.9%, with 10.8% of the surviving patients relapsing after a median of 169 days (IQR 146-281) following the initial TTP event. There were no significant differences in remission status, time to remission, mortality or relapse by HIV status. All HIV positive patients who relapsed had defaulted their antiretroviral therapy (ART). Conclusion: HIV status did not affect patient outcomes in our cohort. ART is important in preventing HIV-associated TTP and relapse. What this study adds: A well-defined demographic of patients with TTP in the ART era in South Africa. Key words: Thrombotic thrombocytopenic purpura, haemolytic anaemia, thrombotic microangiopathy, HIV-associated TTP, ADAMTS13, treatment outcomes, plasma infusion, plasma exchange.